PENGARUH PEMBANGUNAN EKONOMI TERHADAP SUMBER DAYA MANUSIA DI INDONESIA PADA ERA MODERN - Abdillah, Fazli; Ramadhan, Yuda Mulia (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2023)
Poverty in Indonesia is a disease in the economy, so it must be cured or at least reduced. The problem of poverty is indeed a complex and multidimensional problem. Therefore, efforts to eradicate poverty must be carried out in a comprehensive manner, covering various aspects of people's lives, and carried out in an integrated manner. The term poverty appears when a person or group of people is unable to meet the level of economic prosperity which is considered the minimum requirement of a certain standard of living. Poverty is caused by various factors, including the low quality of human development, false economic growth, and disparities/disparities between regions. The poverty rate is a measure that communicates how much consumption is needed to solve a problem. The poverty line used by each nation is unique, so there is no recognized poverty line for the most part. This is due to differences in regions and ways of life. From a strict perspective, need is considered as the absence of cash and merchandise to sustain life. A country's economic growth can be said to be successful if the GDP growth rate is higher than the country's population growth rate. Thus, the economic growth will be more meaningful to people's lives